2004
DOI: 10.1016/j.jallcom.2003.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Structural and spectroscopic studies on the alkali borohydrides MBH4 (M = Na, K, Rb, Cs)

Abstract: Alkali borohydrides MBH 4 and their deuterides have been investigated by X-ray and neutron powder diffraction (M = K, Rb, Cs) and by infrared and Raman spectroscopy (M = Na, K, Rb, Cs). At room temperature the compounds crystallize with a cubic high temperature (HT) structure having Fm3m symmetry in which the [BH 4 ] − complexes are disordered. At low temperature (LT) the potassium compound transforms into a tetragonal low temperature structure having P4 2 /n mc symmetry in which the [BH 4 ] − complexes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
219
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(246 citation statements)
references
References 24 publications
25
219
1
Order By: Relevance
“…There are site and factor group splittings: the degenerate ν 3 mode of F 2 symmetry for the free ion (point group T d ) is split into B + E contributions (site group S 4 ) which transform as A u + B g + E g + E u in C 4h (factor group of the crystal). In addition, by analogy with observations for the analogous [BH 4 ] − ion [34], one can expect the presence of Fermi resonances involving overtones and combination bands of the lower frequency modes observed Combination bands -1000 (Sh) - between 680 and 900 cm −1 . The assignment of these lower frequency modes is not straightforward: there appear four bands at 690, 735, 800 (shoulder) and 900 cm −1 , while only three bands are expected (A u + E u ) for ν 4 , and A u for ν 2 .…”
Section: Vibrationsmentioning
confidence: 59%
“…There are site and factor group splittings: the degenerate ν 3 mode of F 2 symmetry for the free ion (point group T d ) is split into B + E contributions (site group S 4 ) which transform as A u + B g + E g + E u in C 4h (factor group of the crystal). In addition, by analogy with observations for the analogous [BH 4 ] − ion [34], one can expect the presence of Fermi resonances involving overtones and combination bands of the lower frequency modes observed Combination bands -1000 (Sh) - between 680 and 900 cm −1 . The assignment of these lower frequency modes is not straightforward: there appear four bands at 690, 735, 800 (shoulder) and 900 cm −1 , while only three bands are expected (A u + E u ) for ν 4 , and A u for ν 2 .…”
Section: Vibrationsmentioning
confidence: 59%
“…[34,35] The positions of the totally symmetrical stretching mode at 2340 cm -1 in NaBH 4 and 2319 cm -1 in NaBH 4 ·2H 2 O are similar, suggesting a similar B-H bond length in the hydrated and the anhydrous form. Under the experimental conditions of the diffraction experiments, the B-H bond lengths in hydrated and anhydrous NaBH 4 are similar: the average length of the B-H bonds in NaBH 4 ·2H 2 O at 100 K is 1.12(1) Å, whereas in anhydrous NaBH 4 at 200 K the B-H bond length is 1.09(2) Å.…”
Section: Resultsmentioning
confidence: 85%
“…For each, the character of the fundamental in the overtone is slightly higher than 10%. The two components of 2ν 6 being very close in energy, the theoretical anharmonic IR spectrum shown in Figure 5 exhibits finally two bands corresponding to the signature of strong anharmonic couplings that occur in this system. The 2ν 6 is slightly blue-shifted with respect to the ν 4 , in agreement with the picture provided by the experimental investigation, with a relative intensity of about 1:5.…”
Section: Theoretical Methodsmentioning
confidence: 82%
“…This approach was motivated by the study of alkanes with isotopically isolated C-H bonds 5 which revealed both theoretically and experimentally a linear correlation between C-H stretching frequency and bond length. Previously, we have been able to correlate the totally symmetrical B-D stretching mode of the alkali borohydrides with B-D bond length 6 obtained from neutron diffraction data. However, a similar correlation for the B-H stretching mode of the alkali borohydrides fails.…”
Section: Introductionmentioning
confidence: 99%